2006
DOI: 10.1007/s11055-006-0066-0
|View full text |Cite
|
Sign up to set email alerts
|

Gestational hypothyroxinemia and cognitive function in offspring

Abstract: The effects of gestational hypothyroxinemia on the neurointellectual prognosis of children in the first year of life living in an industrial city (megalopolis) with mild iodine deficiency were studied in 13 children of mothers with thyroid hormone-corrected gestational hypothyroxinemia in the first trimester and 10 children of mothers with normal levels of free thyroxine by assessing cognitive functions at ages six, nine, and 12 months using the Gnome mental development scale. The results showed that maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 7 publications
1
16
0
1
Order By: Relevance
“…Subclinical impairment of cognitive and psychomotor development secondary to maternal hypothyroxineamia were found in studies investigating the first half of pregnancy (3538). In several studies, no adverse outcomes were observed when hypothyroxineamia was studied from midpregnancy (39, 40). However, some studies did not find neurodevelopmental problems in children of mothers with hypothyroxinemia (41) or low urinary iodine excretion measured in the first trimester of pregnancy (42).…”
Section: Discussionmentioning
confidence: 99%
“…Subclinical impairment of cognitive and psychomotor development secondary to maternal hypothyroxineamia were found in studies investigating the first half of pregnancy (3538). In several studies, no adverse outcomes were observed when hypothyroxineamia was studied from midpregnancy (39, 40). However, some studies did not find neurodevelopmental problems in children of mothers with hypothyroxinemia (41) or low urinary iodine excretion measured in the first trimester of pregnancy (42).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, thyroid dysfunction during pregnancy increases the risk of adverse maternal and fetal outcomes3739. Subclinical human maternal hypothyroxinemia causes severe neurodevelopmental disorders40, may include changes in blood lipid profile, myocardial function, and neuropsychiatric function4143, and is an independent risk factor in heart failure due to structural and electrical remodeling in the heart24.…”
Section: Discussionmentioning
confidence: 99%
“…The tests that were reviewed in these studies included the WISC, Neonatal Behavioral Assessment Scale, Bayley Scale of Infant Development, McCarthy Scales of Children's Abilities and the Gnome Mental Development Scale (Haddow et al, 1999;Pop, 2001;Pop et al, 2003;Vermiglio et al, 2004;Riano Galan et al, 2005;Kasatkina et al, 2006;Kooistra et al, 2006). By contrast, one study did not find any relationship between maternal T4 levels and cognitive development in children at 6 months (visual recognition memory) and 3 years of age (PPVT and Wide Range of Visual Motor Ability).…”
Section: Iodinementioning
confidence: 99%